Response of Escherichia coli to Prolonged Berberine Exposure - SARIYAR AKBULUT, BERNA; KAZAN, DİLEK; SAYAR, NİHAT ALPAGU (MARY ANN LIEBERT, INC, 2017)
Berberine is a plant-derived alkaloid possessing antimicrobial activity; unfortunately, its efflux through multidrug resistance pumps reduces its efficacy. Cellular life span of Escherichia coli is generally shorter with prolonged berberine exposure; nevertheless, about 30% of the cells still remain robust following this treatment. To elucidate its mechanism of action and to identify proteins that could be involved in development of antimicrobial resistance, protein profiles of E. coli cells treated with berberine for 4.5 and 8 hours were compared with control cells. A total of 42 proteins were differentially expressed in cells treated with berberine for 8 hours when compared to control cells. In both 4.5 and 8 hours of berberine-treated cells, carbohydrate and peptide uptake regimens remained unchanged, although amino acid maintenance regimen switched from transport to synthesis. Defect in cell division persisted and this condition was confirmed by images obtained from scanning electron microscopy. Universal stress proteins were not involved in stress response. The significant increase in the abundance of elongation factors could suggest the involvement of these proteins in protection by exhibiting chaperone activities. Furthermore, the involvement of the outer membrane protein OmpW could receive special attention as a protein involved in response to antimicrobial agents, since the expression of only this porin protein was upregulated after 8 hours of exposure.
Keywords: antimicrobial resistance; berberine; E; coli; protein map; stress response; OUTER-MEMBRANE PROTEINS; UNIVERSAL STRESS-PROTEIN; ISOQUINOLINE ALKALOID BERBERINE; N-ACETYLTRANSFERASE ACTIVITY; FUNCTIONAL-CHARACTERIZATION; ANTIBACTERIAL ACTIVITY; CHAPERONE PROPERTIES; ACID RESISTANCE; GENE-EXPRESSION; IDENTIFICATION